Immunogenicity and safety of measles-mumps-rubella vaccine delivered by disposable-syringe jet injector in India: A randomized, parallel group, non-inferiority trial. Issue 9 (21st February 2018) - ,; Ramaganeshan, D.; Sapru, Amita; Pandit, Anand; Kawade, Anand; Lalwani, Sanjay; Palkar, Sonali; Hanumante, Nita; Malshe, Nandini; Krishna, Vidya; Ingale, S.Y.; Gunale, Bhagwat; et al.
Highlights: We compared MMR vaccine administration by disposable-syringe jet injector (DSJI) and needle and syringe (N-S). The study was conducted in 340 toddlers who had received a measles vaccine at 9 months. On day 35, seropositivity for all three viruses was more than 97% in both the groups. Reactogenicity by both methods was comparable. MMR vaccination via DSJI is as immunogenic and safe as vaccination by N-S. Abstract: Background: We conducted a randomized, non-inferiority, clinical study of MMR vaccine by a disposable-syringe jet injector (DSJI) in toddlers in India in comparison with the conventional administration. Methods: MMR vaccine was administered subcutaneously by DSJI or needle-syringe (N-S) to toddlers (15–18 months) who had received a measles vaccine at 9 months. Seropositivity to measles, mumps, and rubella serum IgG antibodies was assessed 35 days after vaccination. Non-inferiority was concluded if the upper limit of the 95% CI for the difference in the percent of seropositive between groups was less than 10%. Solicited reactions were collected for 14 days after vaccination by using structured diaries. Results: In each study group, 170 subjects received MMR vaccine. On day 35, seropositivity for measles was 97.5% [95% CI (93.8%, 99.3%)] in the DSJI group and 98.7% [95% CI (95.5%, 99.8%)] in the N-S group; for mumps, 98.8% [95% CI (95.6%, 99.8%)] and 98.7% [95% CI (95.5%, 99.8%)]; and for rubella, 98.8% [95% CI (95.6%, 99.8%)] and 100% [95% CI (97.7%, 100.0%)]; none of the differences were significant. The day 35 post-vaccination GMTs in DSJI and N-S groups were measles: 5.48 IU/ml [95% CI (3.71, 8.11)] and 5.94 IU/ml [95% CI (3.92, 9.01)], mumps: 3.83 ISR [95% CI (3.53, 4.14)] and 3.66 ISR [95% CI (3.39, 3.95)] and rubella: 95.27 IU/ml [95% CI (70.39, 128.95)] and 107.06 IU/ml [95% CI (79.02, 145.06)]; none of the differences were significant. The DSJI group reported 173 solicited local reactions and the N-S group reported 112; most were mild grade. Of the total of 156 solicited systemic adverse events, most were mild, and incidence between the two groups was similar. Conclusions: MMR vaccination via DSJI is as immunogenic as vaccination by N-S. Safety profile of DSJI method is similar to N-S except for injection site reactions which are more with DSJI and are well-tolerated. Registration US National Institutes of Health clinical trials identifier – NCT02253407. Clinical trial registry of India identifier – CTRI/2013/05/003702